Astaxanthin nanocapsules with certain high bioavailability and method for manufacturing the same
Patent Information
- Application Number
- JP2023100852
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0011】 本発明が提示する新型アスタキサンチンナノカプセルは、既存商品と比べ、水溶性が高く(78倍に向上)、安定性が高い(90日の加速劣化試験行った結果、保存率が30%向上)。また、アスタキサンチンの生体利用率が45%AUC0-∞向上し、高利用率の化粧品·健康食品製造に適する。さらに、本発明で採用されるアスタキサンチンナノカプセルの製造法は、煩雑な手順がなく、メカノケミストリー法の特徴の一つとして、ジクロロメタン、酢酸ブチルなどの有機溶媒を必要としないことで、有機溶媒による汚染·残留を解決することができる。なお、本製造法は加熱·乾燥の工程がないため、原料の熱劣化を防ぎ、商品の安定性をさらに向上させることができる。
Smart Images

Figure 2025001333000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a new method for producing astaxanthin and related compounds. [Background technology]
[0002] Astaxanthin (AST), whose IUPAC name is 3,3′-dihydroxy-β,β-carotene-4,4′-dione, is a type of xanthophyll found in some birds, aquatic animals, algae, and yeast. AST is the only xanthophyll that can pass through the blood-brain barrier, and has a higher antioxidant effect and free radical scavenging effect than other antioxidants. Astaxanthin currently on the market is primarily used in the following products: (1) Cosmetic ingredients; (2) Health foods and medicines; (3) Food additives.
[0003] Astaxanthin has already been adopted in many products, and development of its applications is also underway. However, several properties of astaxanthin are preventing its further application. (1) AST is a type of oil-soluble xanthophyll with extremely low water solubility. It is primarily absorbed into the skin through fat, but its permeability is easily affected by the structure and type of skin. (2) AST has low stability. Due to its long conjugated unsaturated double bond structure, it is easily oxidized by light, heat, metal ions, oxygen and free radicals during processing, causing it to lose its antioxidant and physiological functions, and even produce harmful substances, which may have adverse effects on the quality of raw materials and products. (3) The bioavailability of AST is low, and when ingested, it is absorbed together with fats and oils, and is easily affected by skin type, diet, and liver and gallbladder function. Furthermore, when the dose of free astaxanthin is increased, it binds with surfactants secreted by the body to form micelles, further reducing the bioavailability of saturated astaxanthin. The above characteristics pose challenges in the application of astaxanthin.
[0004] Conventional nanocapsule manufacturing methods include the melt kneading method, the solvent evaporation method, and the spray drying method. These methods use medium polar organic solvents such as chloroform and butyl acetate in the process, and the residual organic solvent is a problem. In particular, in the case of cosmetics manufacturing, there is a risk of skin irritation. In addition, the spray drying method has a complex process, which results in a large loss of active ingredients in the manufacturing process, making it more difficult to increase the astaxanthin concentration in the capsules. Furthermore, there is also the problem that the deterioration of astaxanthin is promoted by substances obtained by decomposition of xanthophylls such as astaxanthin during manufacturing.
[0005] The mechanochemistry method is of great significance in the production and research of chemical products due to its features such as low energy consumption and no need for organic solvents. It is particularly widely used in the production of nanocapsules of ingredients with poor water solubility and stability, such as retinol acetate, acetylsalicylic acid, and thyme essential oil. In addition, since no organic solvents are used, there is no environmental pollution caused by organic solvents. Furthermore, since there is no need to heat the astaxanthin during production, it is less susceptible to thermal degradation, which plays a major role in improving the concentration and stability of the active ingredient.
[0006] Based on the above, this patent aims to apply mechanochemistry to produce nanocapsules without using solvents or heating, thereby further improving the solubility and permeability of astaxanthin and increasing the bioavailability and stability of the product. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] WJ Su, NE Polyakov, WH Xu, WK Su. Preparation of Astaxanthin Micelles Self-Assembled by a Mechanochemical Method from Hydroxypropyl β-Cyclodextrin and Glyceryl Monostearate with Enhanced Antioxidant Activity[J]. International Journal of Pharmaceutics, 2021, 605:120799. Summary of the Invention [Problem to be solved by the invention]
[0008] Astaxanthin's poor solubility, instability, and low bioavailability significantly limit its inherent antioxidant and free radical scavenging effects. Astaxanthin is a medium polarity component, conventional manufacturing methods require the use of organic solvents to dissolve the raw materials, but at the same time, organic solvent residues affect product production. Furthermore, conventional astaxanthin manufacturing methods involve heating and drying processes, which promote the decomposition of astaxanthin and further reduce its stability. In light of the above, the low bioavailability of astaxanthin, residual organic solvents, and loss of active ingredients need to be improved. [Means for solving the problem]
[0009] As a means for solving the above problems, the present invention provides a new astaxanthin capsule and a method for producing the same. The characteristics of the astaxanthin capsule of the present invention are as follows. (1) Consists of astaxanthin, a polymer carrier, and a surfactant. (2) The polymeric carrier is polyvinylpyrrolidone (average molecular weight 8000), arabinogalactan, β-cyclodextrin or hydroxypropyl-β-cyclodextrin. (3) The surfactant is glycerol monostearate, sucrose fatty acid ester (HLB value 60), soybean lecithin, egg yolk lecithin, or phosphatidylcholine. (4) The mass ratio of astaxanthin to the polymer carrier is 1:10 to 1:100, and preferably 1:30. (5) The mass ratio of astaxanthin to surfactant is 1:1 to 1:10, and preferably 1:6.
[0010] The characteristics of the method for producing astaxanthin nanocapsules of the present invention are as follows: (1) According to the mixing ratio, astaxanthin, polymer carrier, and surfactant are added to a polytetrafluoroethylene (PTFE)-lined ball mill pot, and after uniform dispersion, the contents are crushed in a ball mill and sieved through a 100 mesh sieve. (2) The capacity of the ball mill pot is 600 ml, and the balls (media) are stainless steel balls with a diameter of 15 mm. The filling rate can be 8% to 50% using the balls, and a filling rate of 18% is preferable. (3) The ball mill is of the cylindrical rotation type, and the rotation speed is 50 to 220 rpm, preferably 100 rpm. (4) The grinding time is 0.5 hours to 24 hours, preferably 4 hours. Effect of the Invention
[0011] The new type of astaxanthin nanocapsules proposed by this invention are more water-soluble (78 times more water-soluble) and more stable (a 90-day accelerated deterioration test showed a 30% improvement in preservation rate) than existing products. In addition, the bioavailability of astaxanthin is improved by 45% AUC0-∞, making it suitable for the production of cosmetics and health foods with high utilization rates. Furthermore, the manufacturing method of astaxanthin nanocapsules adopted in this invention does not have complicated procedures, and one of the features of the mechanochemistry method is that it does not require organic solvents such as dichloromethane and butyl acetate, which solves the problem of contamination and residue caused by organic solvents. In addition, since this manufacturing method does not require heating or drying processes, it can prevent thermal deterioration of the raw materials and further improve the stability of the product. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a line graph showing the change in astaxanthin concentration in plasma after administration of different formulations. [Diagram 2] Figure 2 is a bar graph showing the change in astaxanthin concentration in each tissue after administration of different formulations. [Diagram 3] FIG. 3 shows TEM images of Example 2 (FIG. 3a) and Example 3 (FIG. 3b) taken with a transmission electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described with reference to specific examples. However, the scope of the present invention is not limited to the following examples. EXAMPLES
[0014] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of glycerol monostearate, 30 g of β-cyclodextrin, 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 1. EXAMPLES
[0015] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of glycerol monostearate, 30 g of hydroxypropyl-β-cyclodextrin, 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 2. EXAMPLES
[0016] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of glycerol monostearate, 30 g of arabinogalactan, 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 3. EXAMPLES
[0017] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of glycerol monostearate, 30 g of polyvinylpyrrolidone (average molecular weight 8000), 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 4. EXAMPLES
[0018] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of sucrose fatty acid ester, 30 g of hydroxypropyl-β-cyclodextrin, 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 5. EXAMPLES
[0019] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of cholesterol, 30 g of hydroxypropyl-β-cyclodextrin, 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 6. EXAMPLES
[0020] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of soy lecithin, 30 g of hydroxypropyl-β-cyclodextrin, 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 7. EXAMPLES
[0021] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of egg yolk lecithin, 30 g of hydroxypropyl-β-cyclodextrin, 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 8. EXAMPLES
[0022] In a 600 ml ball mill pot lined with PTFE, 1.0 g of astaxanthin, 6.0 g of phosphatidylcholine, 30 g of hydroxypropyl-β-cyclodextrin, 0.11 g of colloidal silicon dioxide, 0.37 g of L-cysteine, and 64 stainless steel balls with a diameter of 15 mm are placed, and the rotation speed is set to 100 rpm and polished for 4 hours. The resulting astaxanthin nanocapsules are referred to as the results of Example 9. EXAMPLES
[0023] Astaxanthin concentration measurement method: (Example 10 and onwards are analyses and tests on the results of the above examples) Procedure for drawing the standard curve for astaxanthin: Take 0.0055 g of astaxanthin (manufactured by Shanghai Aladdin Bio-Chem Technology Co., LTD, purity 98%) and place it in a 50 ml measuring flask, adjust the volume to the desired volume with analytical acetone, mix thoroughly, dilute to 55 μg / ml, 27.5 μg / ml, 22 μg / ml, 11 μg / ml, and 1.1 μg / ml, filter through a filter paper with a pore size of 0.45 μm, and then measure the concentration by HPLC.
[0024] The HPLC measurement conditions were as follows: Measuring device: UV / VIS detector Column: YMC-Carotenoid (4.6×250mm, 5um) Column temperature: 25℃ Flow rate: 1.0ml / min Injection volume: 20μL Mobile phase: Methyl tert-butyl ether, methanol, 1% phosphoric acid in water Measurement wavelength: 474nm The gradient elution conditions are as shown in Table 1.
[0025] [Table 1] The peak areas of different concentrations are obtained and linear regression analysis is performed against the concentration. The regression equation is y = 3.6386x-0.4621 (R^2 = 0.9999) and the applicable concentration range is (1.1μg / ml-55μg / ml). The measurement solution is diluted so that it falls within the standard curve peak area range, and the dilution ratio is V. The peak area PA of the solution is measured by HPLC, and the astaxanthin concentration in the solution is calculated using the following formula (Math 1).
[0026]
number
[0027] Example: Measurement of solubility of astaxanthin nanocapsules For all the results in the examples, solubilization measurements are carried out using the following procedure: 5g of astaxanthin nanocapsules are added to 50ml of distilled water and mixed thoroughly. Then, the mixture is placed in a shaking bath with a temperature setting of 37°C and a shaking speed of 180 rpm, and after 24 hours, the mixture is dissolved to a fully saturated state, and the saturated solution is filtered through a filter paper with a pore size of 0.45 μm. The peak area PA of the filtrate is measured by HPLC, and the concentration of astaxanthin in the saturated solution is calculated using a standard curve. The solubility of the astaxanthin nanocapsules of Examples 1 to 9 is shown in Table 1.
[0028] As shown in Table 2, among the astaxanthin nanocapsules of Examples 1 to 9, the astaxanthin nanocapsules of Example 3 had the best solubility, with a saturated solubility of 914.29 mg / L after 24 hours, which is 78.61 times that of the commercially available sample.
[0029] [Table 2] EXAMPLES
[0030] Example: Method for measuring astaxanthin nanocapsule stability The specific verification method for verifying the stability of the astaxanthin in the examples is as follows. 50 mg of each of Examples 1 to 9 was taken and placed in a 100 ml measuring flask, and the volume was adjusted to constant using acetone. The concentration of astaxanthin C0 (mg / L) was measured using the HPLC measurement method shown in Example 11, and 5 g of each of Examples 1 to 9 was taken and stored in a sealed bag, which was then sealed in an aluminum foil bag. The bags were numbered and placed in a stability tester to verify the stability. The stability tester is set at a temperature of 37°C ± 2°C and a relative humidity of 65% ± 5%. After storing for three months, take 50 mg of the contents and place them in a 100 ml measuring flask, and adjust the volume with acetone. Measure the astaxanthin concentration C0 (mg / L) using the HPLC measurement method shown in Example 11, and calculate the astaxanthin preservation rate Rva% using the following calculation formula (Number 2).
[0031]
number
[0032] The results of the accelerated deterioration storage rates of Examples 1 to 9 are shown in Table 3.
[0033] [Table 3]
[0034] Based on the above, the astaxanthin nanocapsules of Example 3 are the most stable. Taking into consideration the solubility as well as the overall stability, the solubility and stability of the astaxanthin nanocapsules of Examples 2 and 3 are the best, and the solubility and stability are significantly improved compared to the astaxanthin raw material and the commercially available samples. EXAMPLES
[0035] Bioavailability evaluation For the examples 2 and 3, which have good stability and solubility, the bioavailability in SD rats will be verified. In addition, a commercially available astaxanthin capsule (manufactured by BioAstin) will be used as a control. The verification method is as follows. To allow the SD rats to adapt to the experiment, they are kept in an environment with constant temperature and relative humidity and a 12-hour / 12-hour light / dark cycle from one week prior to dosing. Food and water are provided appropriately, and no food is given from 12 hours prior to dosing to 3 hours after dosing. The same dose (0.72mg / kg body weight) of Examples 2 and 3 and the control product are prepared in 10ml of 1% sodium carboxymethylcellulose aqueous solution and orally administered to SD rats. In order to correct for individual differences, a single-group study and a parallel group comparative study are performed. Immediately after administration, and 1, 2, 3, 4, 5, 6, 8, 10, 12, 24, 48, and 72 hours later, blood (200ul) is collected from the orbital venous plexus of SD rats, injected into a centrifuge tube containing 5ml of heparin, mixed thoroughly, and centrifuged for 20 minutes in a centrifuge at 14000r / min, and the supernatant plasma is stored in a freezer at -70℃.
[0036] After thawing the plasma samples obtained in Example 13 at room temperature, away from direct sunlight, take 100 μL of each and place them in a 1.5 ml centrifuge tube, add 200 μL of 1:9 ethanol and tetrahydrofuran solution, stir for 2 minutes, and centrifuge at 14,000 rpm / min for 20 minutes. Take 50 μL of the supernatant, inject nitrogen and evaporate in a 40°C environment, then redissolve using acetone. Using the method described in Example 10, calculate and plot the concentration change of astaxanthin in plasma after injecting different formulations. Enter the concentration values into the pharmacokinetics software DAS2.0 to calculate the blood concentration curve (Figure 1) and pharmacokinetic parameters. The calculated parameters are shown in Table 4.
[0037] [Table 4]
[0038] From the above, it is proven that Examples 2 and 3 have a higher bioavailability of astaxanthin than the commercially available sample. EXAMPLES
[0039] The distribution of astaxanthin in the body is measured: the bioavailability is measured after orally administering the highly soluble and stable Examples 2 and 3 to SD rats, and a commercially available astaxanthin capsule (manufactured by BioAstin) is used as a control. The experimental procedure is as follows. To allow the SD rats to adapt to the experiment, they are kept in an environment with constant temperature and relative humidity and a 12-hour / 12-hour light / dark cycle from one week prior to dosing. Food and water are provided appropriately, and no food is given from 12 hours prior to dosing to 3 hours after dosing. The same dose (7.2mg / kg body weight) of the products in Examples 2 and 3 and the control were prepared in 10ml of 1% sodium carboxymethylcellulose aqueous solution and orally administered to SD rats. Seven days later, all SD rats were euthanized by intraperitoneal administration of ketamine (400mg / kg body weight) and xylazine (20mg / kg body weight), and then the organs such as liver, spleen, kidney, lung, and heart were removed and weighed. Each tissue was homogenized and mixed with distilled water, methanol, 2,6-di-tert-butyl-p-cresol (500mg / L), and chloroform, and homogenized. The homogenized mixture was centrifuged at a rotation speed of 4000 rpm for 15 minutes in an environment of 4°C. The supernatant was collected, evaporated under a nitrogen stream at 40°C, and refluxed with acetone. The concentration change of astaxanthin in each tissue after the different formulations were introduced was plotted using the method shown in Example 10 (Figure 2). EXAMPLES
[0040] Micromorphology of Examples 2 and 3 The micromorphology of the saturated solutions of Example 2 and Example 3 is observed by a transmission electron microscope. The procedure is as follows: About 1 mg of sample is mixed with 3 ml of pure water, sucked up with a capillary tube, and spotted onto a copper plate multiple times. After repeating this process five times, the copper plate is dried and observed and photographed with a transmission electron microscope (HITACHI, HT7700). The accelerating voltage is 100 kV. From the TEM images (Figure 3), it was confirmed that in Example 2 (Figure 3a) and Example 3 (Figure 3b), astaxanthin was integrated with the carrier material to form nanocapsules, thereby realizing improved solubility and stability. [Industrial Applicability]
[0041] This invention is an invention about a method for producing a certain type of astaxanthin nanocapsule. The method involves putting astaxanthin, auxiliary materials, and granules (media) into a 600 ml ball mill, and dispersing the astaxanthin homogenously in the carrier through a mechanochemical reaction at a constant stirring speed to produce astaxanthin nanocapsules. The present invention has the advantage that it can produce astaxanthin nanocapsules under mild conditions, without complicated procedures, and at low cost, and that it does not require organic solvents or complex equipment. These are major advantages in producing astaxanthin nanocapsules, and it is believed that the method has great potential and application value compared to conventional methods.
Claims
1. A method for producing certain astaxanthin nanocapsules. Manufacturing procedure: Astaxanthin, auxiliary materials, and balls (media) are put into a 600ml ball mill and milled at a constant speed. Through a mechanochemical reaction, the astaxanthin is homogenized and dispersed into the carrier, producing astaxanthin nanocapsules. The auxiliary materials consist of carriers, surfactants and glidants. In the solid dispersion, the weight percentages of the components are 2%-3% astaxanthin with a purity of 10%, 80%-85% carrier, 10%-20% surfactant, and 0.2%-0.5% glidant.
2. The method according to claim 1 is characterized in that the carrier is arabinogalactan, polyvinylpyrrolidone (average molecular weight 8000), β-cyclodextrin or hydroxypropyl-β-cyclodextrin.
3. As a feature of the manufacturing method as recited in claim 1, the surfactant is glycerol monostearate, sucrose fatty acid ester, soybean lecithin, egg yolk lecithin, or phosphatidylcholine.
4. The method as recited in claim 1 is characterized in that the glidant is colloidal silicon dioxide, talc or magnesium stearate.
5. The manufacturing method recited in claim 1 is characterized in that the spherical stones (media) are stainless steel balls with a diameter of 5 to 15 mm, and the number of balls added during production is 50 to 300.
6. As a feature of the manufacturing method recited in claim 1, the grinding time is 0.5 hours to 24 hours, and 4 hours is preferable.
7. As a feature of the manufacturing method recited in claim 1, the manufacturing procedure is as follows. Astaxanthin and auxiliary materials (total of 30g to 50g) are placed in a 600ml ball mill pot lined with PTFE, and 64 stainless steel balls with a diameter of 15mm are placed in the pot. The rotation speed is set to 100rpm, and the pot is polished for 4 hours to produce astaxanthin nanocapsules.
Citation Information
Patent Citations
Compositions containing micronutrients with improved antioxidant activity and uses thereof
JP2009543756A
Food composition
JP2017012059A
Neuronal differentiation promoter, and neuronal differentiation promoting composition
JP2019073500A